Comparative assessment of antioxidant activities in Aquilaria malaccensis leaf extracts - Nor Hasima, Mahmod; Zalilawati, Mat Rashid; Mohd Haziq, Abdul Hamid; Abd Manaf, Ali (2017)
We examined antioxidant activities of Aquilaria malaccensis leaves which is a by-product that is normally discarded during cultivation. Crude leaf extracts were obtained from hot extraction by solvents of different polarities; distilled water, ethanol and chloroform. The antioxidant activities of respective crude extract were tested and compared between extraction solvents used using DPPH free radical scavenging activity, ferric-reducing antioxidant power (FRAP) assay, hydrogen peroxide (H2O2) scavenging assay, superoxide (SOD) scavenging activity assay and nitric oxide (NO) scavenging assay. Except for SOD assay, the highest percentage of inhibitions and the lowest IC50 values were achieved in alcohol-based leaf extract which are 85.04 ± 0.43 / 24.72 µg/mL for DPPH, 68.79 ± 0.25 / 71.93 µg/mL for H2O2 and 65.89 ± 0.81 / 68.29 µg/mL for NO assay. The highest FRAP value was also shown in the alcohol-based extracts which is 10.80 ± 0.10 AAE mg/g . In conclusion, the crude extract of Aquilaria malaccensis possess a considerable antioxidant activities regardless of extracting solvents used but the highest was found using ethanol. The activities demonstrated against the various oxidants tested will help to target disease related to the specific oxidants causing it.